COMPARISON OF THE EFFECTIVENESS OF TRADITIONAL AND DIFFERENTIATED CONSERVATIVE TREATMENT METHODS FOR AVASCULAR NECROSIS OF THE FEMORAL HEAD FOLLOWING COVID-19 INFECTION - Karimov M.Yu., Kayumov J.Sh., (Central Asian Journal of Medicine, 2025)
Background: Avascular necrosis (AVN) of the femoral head is an ischemic bone disease that can progress to joint destruction. Post-COVID-19 patients are increasingly being diagnosed with AVN due to virus-induced vascular damage. Traditional treatments often fail to target the altered microvascular environment caused by COVID-19. Objective: To evaluate the clinical and radiological outcomes of a new combination treatment for AVN in post-COVID patients. Methods: A retrospective cohort study was conducted with 198 patients diagnosed with MRI-confirmed Stage 1–3 AVN of the femoral head post-COVID infection. Patients were divided into two groups: conventional therapy (n = 90) and novel combination therapy (n = 108). Clinical, radiographic, and quality-of-life outcomes were assessed over 6 to 18 months. Results: The main group had lower femoral head collapse (10.2% vs. 37.8%), reduced surgical intervention (2.8% vs. 6.7%), and significantly improved SF-36 quality of life scores. MRI scans indicated better structural preservation, and VAS scores for pain improved more markedly in the main group. Conclusion: This novel multimodal treatment combining bisphosphonates and hirudotherapy significantly improves outcomes in AVN following COVID-19, offering a promising non-surgical alternative for early-stage disease.